ADJUSTED F FACTOR FOR MULTIPLE-OUTLET PIPES. - Scaloppi, Edmar José [UNESP] (American Society of Civil Engineers (ASCE), 1988)
An adjusted F factor to compute pressure head loss in pipes having multiple, equally spaced outlets is derived for any given distance from the first outlet to the beginning of the pipe. The proposed factor is dependent on the number of outlets and is expressed as a function of the J. E. Christiansen's F factor. It may be useful to irrigation engineers to estimate friction in sprinkle and trickle irrigation laterals and manifolds, as well as gated pipes.
Keywords: FRICTION; HYDRAULICS - Analysis; IRRIGATION; PRESSURE EFFECTS; F FACTOR; MULTIPLE-OUTLET PIPES; FLOW OF WATER